2009
DOI: 10.1073/pnas.0900589106
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Esx-3 is required for mycobactin-mediated iron acquisition

Abstract: The Esx secretion pathway is conserved across Gram-positive bacteria. Esx-1, the best-characterized system, is required for virulence of Mycobacterium tuberculosis, although its precise function during infection remains unclear. Esx-3, a paralogous system present in all mycobacterial species, is required for growth in vitro. Here, we demonstrate that mycobacteria lacking Esx-3 are defective in acquiring iron. To compete for the limited iron available in the host and the environment, these organisms use mycobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
321
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(334 citation statements)
references
References 46 publications
12
321
1
Order By: Relevance
“…However, the uptake of transferrin iron observed in our experiments was rapid with increased cellular iron levels observed within 6 h for M.tb H37Ra and within 1 h for M. smegmatis strains. Crucially, the M. smegmatis Desx-3 strain that is unable to utilize mycobactin 35 retained its ability to acquire transferrin iron to levels comparable with that of the wild-type strain. Siderophore synthesis occurs only after culture in iron-free media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the uptake of transferrin iron observed in our experiments was rapid with increased cellular iron levels observed within 6 h for M.tb H37Ra and within 1 h for M. smegmatis strains. Crucially, the M. smegmatis Desx-3 strain that is unable to utilize mycobactin 35 retained its ability to acquire transferrin iron to levels comparable with that of the wild-type strain. Siderophore synthesis occurs only after culture in iron-free media.…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH was also identified in various fractions of M. smegmatis. To assess whether (i) transferrin-mediated uptake exists across mycobacterial species and (ii) whether mycobactin is essential for iron uptake from transferrin, we utilized the M. smegmatis Desx-3 that lacks the esx-3 secretion system and is therefore incapable of mycobactin-mediated iron uptake 35 . M. smegmatis wild-type and M. smegmatis Desx-3 strains demonstrated no difference in binding of transferrin ( Supplementary Fig.…”
Section: Localization Of Gapdh In Different Cellular Fractionsmentioning
confidence: 99%
“…46 However, esxH has been the only antigen of the TB10.4 esx subfamily targeted as a vaccine candidate because it is strongly recognized by BCG-vaccinated individuals and by 70% of TB patients. 23 Nevertheless, we show immunological evidence that simultaneously targeting all members of this subfamily in future vaccine approaches may provide better efficacy against TB.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The locus is essential for the growth of M. tuberculosis and the attenuated M. bovis strain used in BCG. 5 The team found that unlike M. tuberculosis and BCG, the more distant relative M. smegmatis could grow normally when esx-3 was deleted, and thus they selected the strain to study the locus' role.In mouse models of M. smegmatis infection, an esx-3-deleted strain was unable to evade the host innate immune system, whereas wildtype and esx-1-deleted strains did not elicit a strong innate immune response. Moreover, the esx-3-deleted strain had attenuated virulence.…”
mentioning
confidence: 99%
“…3,4 The locus is essential for the growth of M. tuberculosis and the attenuated M. bovis strain used in BCG. 5 The team found that unlike M. tuberculosis and BCG, the more distant relative M. smegmatis could grow normally when esx-3 was deleted, and thus they selected the strain to study the locus' role.…”
mentioning
confidence: 99%